Henry P. Newman. Hamburger Großkaufmann und Mäzen - Busold, Stefanie (Mäzene für Wissenschaft, 2012)
Henry P. Newman loved fine arts: In the house of the Hamburg grain wholesaler who introduced revolutionary unloading techniques on his company quay, painters and poets were frequent guests. For many years the merchant banker assembled an extraordinary collection of exquisite paintings. Among them were works by French and German impressionists. When World War I broke out, Henry P. Newman donated the hospital train C1 and accompanied it to Bulgaria in the winter of 1915/16. Although being an educated art lover, Newman was also committed to science. He was a member of the first board of trustees of the Hamburg Scientific Foundation. This biography traces the life of this man, who - contrary to the prevailing self-conception of the Hanseatic merchant team - devoted himself to his profession with dedication and expert knowledge of art.